Correlation between cardiometabolic index and psoriasis: a cross-sectional analysis using NHANES data - Li, Mengxue; Gan, Yixiao; Cheng, Hong; Wang, Zhicheng (Frontiers in Physiology, 2025)
BackgroundPsoriasis is closely associated with metabolic health. The Cardiometabolic Index (CMI) is an innovative and easily obtainable metric employed to assess cardiometabolic health. This study aims to examine the possible relationship between CMI and psoriasis.MethodsData from four successive cycles of the National Health and Nutrition Examination Survey (NHANES) conducted between 2003–2004 and 2009–2014 were employed. This encompassed adults with self-reported psoriasis diagnoses and comprehensive information necessary for calculating the CMI. The calculation formula for CMI is Triglycerides (TG)/High-density lipoprotein cholesterol (HDL-C) × WHtR (WHtR = waist circumference/height). A multivariable logistic regression model was utilized to examine the linear relationship between CMI and psoriasis. Subgroup analyses were conducted to investigate potential contributing factors. The linear relationship was further established using smooth curve fitting.ResultsThis study, utilizing NHANES data, comprised a cohort of 7,327 American adults. The multivariable logistic regression analysis indicated that in the fully adjusted model, people with the greatest CMI had a 71% increased probability of psoriasis relative to those with the lowest CMI (OR = 1.71; 95% CI, 1.11–2.61, P < 0.05). Smooth curve fitting demonstrated a linear connection between CMI and psoriasis (P < 0.05). The subgroup analysis revealed no significant interactions between CMI and specific subgroups (all interactions P > 0.05).ConclusionOur research indicates a substantial linear correlation between CMI and psoriasis in American adults. This method facilitates the identification of groups at increased risk for psoriasis, therefore guiding therapeutic solutions and public health activities to improve metabolic and dermatological health outcomes.